Notes on the grasshopper genera Longgenacris You & Li, 1983 and Fruhstorferiola Willemse, 1922 (Orthoptera: Acrididae: Melanoplinae) with proposal of a new synonym - Jiang, Bing; Wang, Haojie; Storozhenko, Sergey Yu.; Huang, Jianhua (Zootaxa, 2019)
A taxonomic review of the genus Longgenacris You & Li, 1983 is provided, the taxonomic position of the genus is discussed briefly and clarified; the original placement of the genus in the subfamily Melanoplinae is confirmed. Type species of the genus Fruhstorferiola Willemse, 1922 is redescribed and new synonymy is proposed: Fruhstorferiola tonkinensis (Willemse, 1921) = Longgenacris rufiantennus Zheng et Wei, 2003, syn. nov.